HEDGES USED BY INDONESIAN ELT STUDENTS IN WRITTEN AND SPOKEN DISCOURSES - Rida, Asfina; Kadarisman, A. Effendi; Astuti, Utari Praba (Universitas Pendidikan Indonesia, 2018)
Hedging expression is considered an important interactional metadiscourse device which shows the writer’s/speaker’s degree of confidence in the truth of a proposition and his/her attitude to the readers or listeners in academic discourse. Although considerable research on hedges has been undertaken, there have been virtually no studies on hedges in spoken discourse in educational contexts. To fill this gap, this study aims at describing and comparing the use of hedges by Indonesian ELT students in written and spoken discourses. This study is descriptive qualitative in nature. The research subjects were 20 ELT graduate students registered in 2015 at a state university in East Java, Indonesia. The sources of data were the students’ thesis proposals and thesis proposal presentations, particularly the ‘background of the study’ section. As such, the study used a corpus-based approach which utilized concordance software, i.e. AntConc (3.4.4), to examine the frequency of hedges based on types. The use of hedges was categorized on the basis of hedges taxonomy adapted from Salager-Meyer (1994) and Hyland (2005). The findings of this study revealed that (i) in terms of types and frequency, the patterns of the use of hedges types (from the most to the least frequently used) by ELT students in both corpora were almost similar: WD: S–Ap–Em–Ex–Ch, and SD: S–Ap–Ex–Em–Ch (see Table 2 for legends); (ii) ELT students employed more hedges in written discourse than in spoken discourse; and (iii) approximately 65% of hedges variants provided in the taxonomy were employed by ELT students in written and spoken discourses. On the basis of the results of the study, the discourse mode (written or spoken) can be a factor that affects the use of hedges in academic discourse.